Exploration of Figurative Language in the Poetry Collection Manifesto Koplo by Aditya Ardi N. - Siti Maisaroh; Susi Darihastining; Heny Sulistyowati; Akhmad Sauqi Ahya (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study focuses on the exploration of figurative language or literary devices in the poetry collection Manifesto Koplo by Aditya Ardi N. The aim of this research is to explore the figurative language used in the collection. The method employed is descriptive, with a stylistic approach. The data source consists of 20 poems selected from the 69 poems in Manifesto Koplo. The research procedure includes: (1) carefully reading and understanding the poems; (2) identifying and marking data within the poems used as the research source, supported by data collection instruments; (3) classifying the data that demonstrate the author’s figurative language according to the research focus; (4) analyzing and describing the data based on the research objectives; and (5) drawing conclusions regarding the figurative language found. The findings indicate that the use of language in the poetry collection reflects the author’s creativity, which is meticulous and detailed in every stanza. The uniqueness of the author is evident in the titles of the poems, which are all related to elements surrounding the dangdut koplo music community, such as the names of female singers, musicians, guitars, drummers, flutes, and so on. The 20 poems analyzed contain highly diverse and aesthetically pleasing figurative language that enhances the distinctive style and originality of the author’s thoughts. The figurative language employed in the collection includes simile, personification, hyperbole, metaphor, paradox, and parallelism. Among these, personification is the most dominant. Notably, two poems—Biduanita Ardila Putri and Jaran Goyang—each contain four types of figurative language simultaneously. This demonstrates the variety and richness of figurative expressions that the author utilizes to beautify the poems while reinforcing their uniqueness and originality.